Cotranscriptional histone H2B monoubiquitylation is tightly coupled with RNA polymerase II elongation rate - Fuchs, Gilad; Hollander, Dror; Voichek, Yoav; Ast, Gil; Oren, Moshe

(untitled) (Genome Research, 2014)
Various histone modifications decorate nucleosomes within transcribed genes. Among these, monoubiquitylation of histone H2B (H2Bub1) and methylation of histone H3 on lysines 36 (H3K36me2/3) and 79 (H3K79me2/3) correlate positively with gene expression. By measuring the progression of the transcriptional machinery along genes within live cells, we now report that H2B monoubiquitylation occurs cotranscriptionally and accurately reflects the advance of RNA polymerase II (Pol II). In contrast, H3K36me3 and H3K79me2 are less dynamic and represent Pol II movement less faithfully. High-resolution ChIP-seq reveals that H2Bub1 levels are selectively reduced at exons and decrease in an exon-dependent stepwise manner toward the 3′ end of genes. Exonic depletion of H2Bub1 in gene bodies is highly correlated with Pol II pausing at exons, suggesting elongation rate changes associated with intron–exon structure. In support of this notion, H2Bub1 levels were found to be significantly correlated with transcription elongation rates measured in various cell lines. Overall, our data shed light on the organization of H2Bub1 within transcribed genes and single out H2Bub1 as a reliable marker for ongoing transcription elongation.